Charting a Course for Implementation Research in Oral Health. (October 2016) - Clark, D.B.; Ducharme, L.
Knowledge Transfer Statement: This article provides an overview of implementation science and outlines NIDCR's interest and commitment to research that decreases time from development through implementation of evidence-based oral health interventions.